Oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel as well as preparation method and application thereof

By introducing orientation degumming fibers into polyvinyl alcohol hydrogels and adopting thermal annealing process, the problem of insufficient mechanical properties of traditional hydrogel materials is solved, and the mechanical properties of intervertebral disc repair materials are improved, which can more effectively simulate the mechanical microenvironment of the fiber annulus.

CN119875162AInactive Publication Date: 2025-04-25ZHEJIANG UNIV OF TECH +2

Patent Information

Application Number
CN202510389169.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the weak mechanical properties of traditional hydrogel materials, they cannot effectively simulate the mechanical microenvironment of the fibrous annulus and cannot meet the toughness and modulus requirements required for intervertebral disc repair.

Method used

The polyvinyl alcohol hydrogel is fiber-reinforced by introducing oriented degumming fibers, and the nanocrystallisation threshold of the hydrogel is enhanced by thermal annealing process to enhance the mechanical properties of the material.

Benefits of technology

The fracture toughness and crack propagation resistance of the hydrogel are improved, and the mechanical microenvironment of the fibrous annulus can be more effectively simulated and meet the needs of intervertebral disc repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875162A_ABST
    Figure CN119875162A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogel, in particular to oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel as well as a preparation method and application thereof.The hydrogel comprises degummed silk fiber and polyvinyl alcohol, has an anisotropic structure and can effectively enhance the fracture toughness and crack propagation resistance of the hydrogel. Through the assembly of the bionic fibrous ring structure, the multi-scale architecture of the natural intervertebral disc fibrous ring is simulated, the native fibrous ring structure is copied, and the mechanical microenvironment of the fibrous ring is simulated. The hydrogel and the artificial intervertebral disc have high toughness, long-term stability and biocompatibility, are particularly suitable for intervertebral disc repair, can stably bear biological load for a long time in intervertebral disc repair, and have relatively high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogels, and in particular to oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel, a preparation method and application thereof. Background Art

[0002] With the aging of the population, spinal diseases have gradually become the main cause of disability in developed countries, especially low back pain caused by lumbar intervertebral disc degeneration (IVDD). The characteristics of degenerative discs are the rupture of collagen fibers in the annulus fibrosus, dehydration of the nucleus pulposus and reduced elasticity, which leads to loss of disc function and may cause extravasation of the nucleus pulposus, compression of nerve roots, and chronic pain. As an important component of the intervertebral disc, the annulus fibrosus (AF) plays a key role in maintaining disc function and spinal stability.

[0003] At present, traditional treatments mainly include non-surgical therapies (such as physical therapy and drug therapy) and surgical interventions (such as discectomy and spinal fusion). Although these methods can relieve symptoms, they cannot fundamentally repair the structure of the intervertebral disc, especially the damage to the annulus fibrosus. The key to existing repair methods is to be able to mimic the structure and mechanical properties of the annulus fibrosus in order to restore the normal function of the intervertebral disc.

[0004] As a three-dimensional polymer network, hydrogel has similar physical and chemical properties to biological tissues and is widely used in drug delivery, tissue engineering and biomedical fields. In the prior art, traditional hydrogel materials cannot effectively simulate the mechanical microenvironment of the annulus fibrosus due to their weak mechanical properties, and cannot meet the toughness and modulus requirements required for intervertebral disc repair. Therefore, it is urgent to develop a new type of hydrogel material that can provide the required mechanical properties in the process of intervertebral disc repair, especially to achieve a balance between mechanical strength and toughness.

[0005] Chinese invention patent application CN200710190413.0 discloses a method for preparing nanofibers, using silk fibroin and polyvinyl alcohol as raw materials, adding silver-based inorganic salts, and electrostatic spinning through silver electrodes to obtain nano-scale antibacterial fibers. The fiber process prepared by this method is relatively complicated and the cost of industrial production is high. Silk fibroin is a high-molecular fiber protein extracted from silk fibers by chemical or physical methods. It loses its fiber structure and its mechanical strength is significantly reduced, resulting in the mechanical properties of the prepared nanofibers being weak, especially under long-term load. In addition, the sustained release mechanism of the silver element ions of the nano-scale antibacterial fibers prepared by this method is not clear, which limits its medical use in biomedical materials.

[0006] Chinese invention patent application CN202310268430.0 discloses the preparation and application of a cartilage-mimicking hydrogel electrode, which uses interwoven silk nanofibers as a "network", polyvinyl alcohol as a "matrix", and a hydrogel electrode loaded with carbon nanotubes and polypyrrole to simulate cartilage to build a stretchable high-performance supercapacitor. Silk nanofibers are made by stripping degummed silk fibers with a low eutectic solvent. The increased specific surface area can load more carbon nanotubes, which enhances the conductivity of the material. However, the capacitor prepared by this method cannot achieve a balance between mechanical properties and conductivity at the same time, and the mechanical properties are weak, with a tensile strength of only 1.3 MPa and a modulus of only 1.22 MPa. The preparation process is complex and highly equipment-dependent, which limits industrial applications. Hydrogel electrolytes are easily affected by environmental humidity, which may introduce biological toxicity risks and reduce their use value.

[0007] In previous studies, researchers have improved the mechanical properties of PVA hydrogels by combining silk fibroin or silk nanofibers with polyvinyl alcohol, and have given the materials specific functionality through subsequent treatments such as electrospinning, electroplating, or surface modification. However, other studies have overlooked the possibility of directly introducing degummed silk fiber structures to enhance the mechanical properties of PVA hydrogels. Silk fibers have excellent mechanical properties, with a breaking strength of approximately 265-350 MPa, an elongation at break of 15-25%, and a high elastic modulus, which is close to that of biological tendons. They are easy to prepare and can be obtained by simple hot alkali degumming. In addition, there is still a lack of research on how to add degummed silk fibers to hydrogels based on polyvinyl alcohol. At the same time, the effects of the ratio of PVA to SF and the thermal annealing temperature on hydrogel films are unknown.

[0008] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0009] The purpose of the present invention is to solve the problem that traditional hydrogel materials have weak mechanical properties and cannot effectively simulate the mechanical microenvironment of the annulus fibrosus and cannot meet the toughness and modulus requirements for intervertebral disc repair. Provided are oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel, preparation method and application.

[0010] In order to achieve the above object, the present invention discloses an oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel, wherein the hydrogel comprises degummed silk fibers and polyvinyl alcohol, wherein the mass ratio of the degummed silk fibers to the polyvinyl alcohol is 1:1 to 1:4, and the hydrogel has an anisotropic structure.

[0011] The present invention also discloses a method for preparing the above-mentioned oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel, and the specific method is as follows: the degummed silk fibers are oriented and then degummed, combed and dispersed evenly with a comb, and then placed in a polytetrafluoroethylene mold, and polyvinyl alcohol solution is poured into it, and evaporated on a constant temperature heating platform to obtain a hydrogel dry film, and then hot-pressed on a hot press, and finally swelled and balanced in deionized water to obtain a hydrogel.

[0012] The molecular weight of the polyvinyl alcohol solution is 1000-500000, the concentration of the polyvinyl alcohol solution is 0.2-20wt%, the mass ratio of the degummed silk fiber to the polyvinyl alcohol solution is 1:1-1:4, and the degummed silk fiber is obtained by degumming white silk.

[0013] The temperature of the constant temperature heating platform is 30-90°C, and the temperature of the thermal annealing is 90-150°C.

[0014] The present invention also discloses the use of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel in the preparation of an artificial intervertebral disc. The specific preparation method comprises the following steps:

[0015] S1, multiple sheets of oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel were stacked and bonded with polyvinyl alcohol as glue;

[0016] S2, compacting the laminated oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel with a breathable ceramic sheet, placing it in an oven for drying, and surrounding the laminated layer after compaction and drying into an artificial fiber ring;

[0017] S3, thermally annealing the artificial annulus fibrosus and allowing it to swell in deionized water, and dripping agarose solution into the artificial annulus fibrosus to obtain an artificial intervertebral disc hydrogel material.

[0018] In the step S1, the stacking angle between the multiple pieces of oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel is 30°, 45° or 60°.

[0019] In the step S1, the glue is a 10 wt% polyvinyl alcohol aqueous solution.

[0020] In the step S2, the drying temperature is 60°C and the thermal annealing temperature is 110°C.

[0021] In step S3, the concentration of the agarose solution is 5 wt %.

[0022] The invention also discloses the application of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel in the field of medical materials.

[0023] The present invention introduces degummed silk fibers to reinforce the hydrogel, and through the oriented structure, the material has an anisotropic structure, which can effectively enhance the fracture toughness and crack propagation resistance of the hydrogel. Then, the nanocrystallization threshold of polyvinyl alcohol in the hydrogel is enhanced by the process of thermal annealing. As a reversible crosslinking point, the nanocrystallization threshold can effectively improve the energy dissipation capacity of the hydrogel and alleviate the sensitivity of the hydrogel to cracks. At the same time, the process of thermal annealing causes the random curling and spiral structure of the protein in the degummed silk fiber to transform into a β-sheet structure. The two work synergistically to achieve the improvement of the mechanical properties of the hydrogel. Subsequently, the application of the material is designed by splitting the fiber ring structure, and the hydrogel with a one-dimensional oriented structure is transformed into a three-dimensional artificial intervertebral disc through a three-dimensional structuring process, which has good biomedical potential.

[0024] Compared with the prior art, the beneficial effects of the present invention are:

[0025] 1. The present invention uses silk fiber and polyvinyl alcohol with good biocompatibility as basic elements, so that the material has good biocompatibility;

[0026] 2. The present invention enhances the fracture toughness of the material by introducing a fiber orientation structure;

[0027] 3. The process of the present invention is simple, the price is low, and it can be industrialized;

[0028] 4. The bionic intervertebral disc hydrogel material of the present invention has better support and long-term stability than other repair materials, and can better repair the defective part of the intervertebral disc;

[0029] 5. The intervertebral disc hydrogel material of the present invention has an oriented structure, which is beneficial to the adsorption and proliferation of fibroblasts and the attachment and growth of tissues;

[0030] 6. The present invention prepares intervertebral disc repair materials by simulating the multi-layer collagen fiber structure of the natural annulus fibrosus with a polyvinyl alcohol (PVA) hydrogel matrix reinforced with degummed silk fibers (SF). The obtained material has improved mechanical properties compared with the hydrogel materials currently used to repair intervertebral discs. The fiber reinforcement method allows the material to have good fracture toughness. The multi-layer collagen fiber structure of the biomimetic natural annulus fibrosus replicates the natural annulus fibrosus mechanical microenvironment, which is of great significance for the long-term repair of the intervertebral disc. The high biocompatibility and low cost of silk fiber and polyvinyl alcohol can realize the low-cost and simplified preparation of a new generation of intervertebral disc repair materials with good safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Polyvinyl alcohol hydrogel reinforced with oriented degummed silk fibers, and a method for preparing an artificial intervertebral disc based on the hydrogel;

[0032] Figure 2 The uniaxial tensile stress-strain curves of the hydrogels prepared in Examples 2, 3, 4, and 5;

[0033] Figure 3 The stress-strain statistical results of the hydrogels prepared in Examples 2, 3, 4, and 5;

[0034] Figure 4 Statistical results of elastic modulus and work of fracture of the hydrogels prepared in Examples 2, 3, 4, and 5;

[0035] Figure 5 The morphology of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel prepared in Example 2 is shown;

[0036] Figure 6 This is a scanning electron microscope image of the hydrogel prepared in Example 2;

[0037] Figure 7 This is a scanning electron microscope image of the hydrogel prepared in Example 3;

[0038] Figure 8 This is a scanning electron microscope image of the hydrogel prepared in Example 4;

[0039] Fig. 9 This is a scanning electron microscope image of the hydrogel prepared in Example 5;

[0040] Fig.10 Fourier transform infrared spectra of the hydrogels prepared in Examples 2, 3, 4, and 5;

[0041] Fig.11 Fourier transform infrared spectra of the hydrogels prepared in Examples 2, 3, 4, and 5 at 3000 cm -1 ~3600cm -1 Peak separation result diagram of the peak;

[0042] Fig.12 The Lieber transform infrared spectra of the hydrogels prepared in Examples 2, 3, 4 and 5 are shown at 1600 cm -1 ~1700cm -1 The result diagram of calculating the secondary structure of proteins in degummed silk fibers.

[0043] Fig.13 The morphology display picture of the artificial intervertebral disc prepared in Example 1;

[0044] Fig.14 Prepare the artificial intervertebral disc Mic CT image for Example 1;

[0045] Fig.15 Polarized light microscopic picture of the vertical section of the artificial intervertebral disc prepared in Example 1;

[0046] Fig.16 Scanning electron microscope image of the artificial intervertebral disc prepared for Example 1;

[0047] Fig.17 Compression curve of the artificial intervertebral disc prepared in Example 1;

[0048] Fig.18 These are images of cell survival / death after 1, 3, and 5 days of co-culture with fibroblasts in Examples 1 and 5. DETAILED DESCRIPTION

[0049] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0050] Example 1

[0051] Weigh 20 g of polyvinyl alcohol (molecular weight 146,000-186,000) powder and mix with 980 mL of deionized water, heat and stir in an oil bath at 110 °C for 12 h to prepare a 2 wt% PVA solution;

[0052] Weigh 10.6 g of sodium carbonate solution and dissolve it in deionized water. The volumetric flask is calibrated to obtain a 0.25 M uniform sodium carbonate solution. The white silk is wound and arranged by a winding machine. The two ends are fixed with clips. The white silk is degummed in 0.25 M sodium carbonate solution in a 90 ° C water bath for 10 min. After degumming, it is washed with deionized water for more than 10 times to remove the residual sodium carbonate in the silk until there is no obvious foam in the silk. Finally, the degummed silk is dried in a 37 ° C oven;

[0053] Take out the dried silk, comb the gathered silk with a comb, comb the silk evenly with combs of different thicknesses, weigh 0.5 g of combed silk and place it in a polytetrafluoroethylene mold (10 cm×10 cm×5 mm), clamp the two ends of the silk with clips to make the silk have consistent directionality, then pour 50 mL of 2 wt% PVA solution into the mold, and dry the mold on a 40°C constant temperature heating platform for 24 h;

[0054] The formed PVA-SF film was thermally annealed in an oven at 110° C. for 30 min to obtain a thermally annealed PVA-SF film;

[0055] Two pieces of PVA-SF membrane were cut into fibers and arranged into long strips with angles of +30° and -30°. The two membranes were bonded in the middle with 10 wt% PVA as glue for stacking. Then, the stacked hydrogel dry membrane was compacted with a breathable ceramic sheet, placed in an oven and dried at 60°C for 6 h, and then taken out. A layer of 10 wt% PVA solution was applied to the surface of the material to form an artificial fiber ring. The material was dried in an oven at 60°C for 12 h and then thermally annealed at 110°C for 30 min. The material was swelled to equilibrium in deionized water and cut into a suitable height. Then, agarose solution was dripped into the artificial fiber ring and finally cooled to room temperature to obtain an artificial intervertebral disc hydrogel material (named AF-NP).

[0056] Under the conditions of Example 1, from Fig.13 It can be seen from the figure that the macroscopic morphology of the artificial intervertebral disc material (AF-NP) is roughly cylindrical in shape, and it can fit well in the middle of the spine. Fig.14 From the Mic CT images, AF-NP presents a multi-layer assembled cylindrical morphology. Fig.15 The polarization results show that the fiber orientations of every two layers of AF-NP are different, with an angle of 60°. Fig.16 Scanning electron microscopy images further illustrate that AF-NPs are multi-layered concentric circles. Fig.17 The compressive capacity of AF-NPs was demonstrated. AF-NPs showed excellent compressive properties and could reach a compressive stress of 9.83 MPa at 10% strain. Fig.18 The biocompatibility of AF-NPs was evaluated. The material was co-cultured with fibroblasts and cell death / survival was imaged using fluorescence microscopy, which showed that AF-NPs had good biocompatibility.

[0057] Example 2

[0058] Weigh 20 g of polyvinyl alcohol (molecular weight 146,000-186,000) powder and mix with 980 mL of deionized water, heat and stir in an oil bath at 110 °C for 12 h to prepare a 2 wt% PVA solution;

[0059] Weigh 10.6 g of sodium carbonate solution and dissolve it in deionized water. The volumetric flask is calibrated to obtain a 0.25 M uniform sodium carbonate solution. The white silk is wound and arranged by a winding machine. The two ends are fixed with clips. The white silk is degummed in 0.25 M sodium carbonate solution in a 90 ° C water bath for 10 min. After degumming, it is washed with deionized water for more than 10 times to remove the residual sodium carbonate in the silk until there is no obvious foam in the silk. Finally, the degummed silk is dried in a 37 ° C oven;

[0060] Take out the dried silk, comb the gathered silk with a comb, comb the silk evenly with combs of different thicknesses, weigh 0.5 g of combed silk and place it in a polytetrafluoroethylene mold (10 cm×10 cm×5 mm), clamp the two ends of the silk with clips to make the silk have consistent directionality, then pour 50 mL of 2 wt% PVA solution into the mold, and dry the mold on a 40°C constant temperature heating platform for 24 hours;

[0061] The formed PVA-SF membrane was thermally annealed in an oven at 110° C. for 30 min to obtain a thermally annealed PVA-SF membrane, and then immersed in deionized water for 2 hours to obtain a PVA-SF hydrogel (named APS).

[0062] Under the conditions of Example 2, Figure 5 The macroscopic morphology of the prepared APS is shown. The APS hydrogel is flexible and can be curled and twisted under external force. Figure 6 The scanning electron microscopy results show that the APS hydrogel has a good fiber orientation microstructure. We tested the tensile mechanical properties of the hydrogel by performing a uniaxial tensile test. Figure 2 This is the tensile stress-strain curve of APS hydrogel. Figure 3 and Figure 4 The statistical results show that the APS hydrogel has a fracture strain of 61.83%, a tensile strength of 57.11 MPa, an elastic modulus of 159.36 MPa, and a thermal conductivity of 27.19 MJ / m 3 The fracture work of the composite material is low, indicating that it has excellent mechanical properties. Fig.10 The Fourier transform infrared spectrum of the hydrogel is shown in Figure 3. -1 and 3370 cm -1 The peak area ratio at is used to quantify the hydrogen bonding interaction between polyvinyl alcohol and water molecules in the material, and the content of protein secondary structure is analyzed to analyze the mechanical properties of the material. Fig.11 It can be concluded that the hydrogel has a peak at 3210 cm -1 The peak area at 3370 cm-1 accounts for 47.69%, and the peak area at 3370 cm-1 accounts for 47.69%. -1 The peak area at 3210 cm-1 accounts for 52.31%. -1 The peak area accounts for the largest proportion, so its performance is the strongest. Fig.12 It can be seen that under the conditions of Example 2, the content of β-sheet in SF is 42.13%, the content of random curl and spiral is 13.03%, and the content of β-turn is 44.84%. The APS hydrogel has a higher content of β-sheet and better mechanical properties.

[0063] Example 3

[0064] Weigh 20 g of polyvinyl alcohol (molecular weight 146,000-186,000) powder and mix with 980 mL of deionized water, heat and stir in an oil bath at 110 °C for 12 h to prepare a 2 wt% PVA solution;

[0065] Weigh 10.6 g of sodium carbonate solution and dissolve it in deionized water. The volumetric flask is calibrated to obtain a 0.25 M uniform sodium carbonate solution. The white silk is wound and arranged by a winding machine. The two ends are fixed with clips. The white silk is degummed in 0.25 M sodium carbonate solution in a 90 ° C water bath for 10 min. After degumming, it is washed with deionized water for more than 10 times to remove the residual sodium carbonate in the silk until there is no obvious foam in the silk. Finally, the degummed silk is dried in a 37 ° C oven;

[0066] Take out the dried silk, comb the gathered silk with a comb, comb the silk evenly with combs of different thicknesses, weigh 0.5 g of combed silk and place it in a polytetrafluoroethylene mold (10 cm×10 cm×5 mm), clamp the two ends of the silk with clips to make the silk have consistent directionality, then pour 50 mL of 2 wt% PVA solution into the mold, and dry the mold on a 40°C constant temperature heating platform for 24 h;

[0067] The formed PVA-SF membrane was taken out and then soaked in deionized water for 2 hours to obtain PVA-SF hydrogel (named PS).

[0068] Under the conditions of Example 3, from Figure 7 It can be seen that PS hydrogel has a fiber-oriented structure. Figure 2 is the tensile stress-strain curve of PS hydrogel. Figure 3 and Figure 4 The statistical results show that the PS hydrogel has a fracture strain of 73.61%, a tensile strength of 45.74 MPa, an elastic modulus of 108.98 MPa, and a thermal conductivity of 30.13 MJ / m 3 The work of fracture. Fig.10 The Fourier transform infrared spectrum of the hydrogel. Fig.11 According to the analysis results, the hydrogel has a -1 The peak area at 3370 cm-1 accounts for 45.62%, and the peak area at 3370 cm-1 accounts for 45.62%. -1 The peak area at 3210 cm accounts for 54.38%. -1 The peak area at occupies a smaller proportion, indicating that the hydrogel prepared under the conditions of Example 2 has a smaller interaction force between PVA and PVA molecules. Fig.12It can be seen that under the conditions of Example 3, the β-sheet content of SF is 25.26%, the random curl and spiral content is 29.80%, and the β-turn content is 44.94%. Compared with Example 2, its β-sheet accounts for a smaller proportion and its mechanical properties are weaker.

[0069] Example 4

[0070] Weigh 20 g of polyvinyl alcohol (molecular weight 146,000-186,000) powder and mix with 980 mL of deionized water, heat and stir in an oil bath at 110 °C for 12 h to prepare a 2 wt% PVA solution;

[0071] Weigh 10.6 g of sodium carbonate solution and dissolve it in deionized water. The volumetric flask is calibrated to obtain a 0.25 M uniform sodium carbonate solution. The white silk is degummed in the 0.25 M sodium carbonate solution in a 90 °C water bath for 10 min. After degumming, the silk is washed with deionized water for more than 10 times to remove the residual sodium carbonate in the silk until there is no obvious foam on the silk. Finally, the degummed silk is dried in a 37 °C oven.

[0072] Take out the dried silk, comb the gathered silk with a comb, comb the silk evenly with combs of different thicknesses, weigh 0.5 g of combed silk and place it in a polytetrafluoroethylene mold (10 cm×10 cm×5 mm), evenly disperse the silk to make it chaotic and disordered, then pour 50 mL of 2 wt% PVA solution into the mold, and dry the mold on a 40°C constant temperature heating platform for 24 h;

[0073] The formed PVA-SF membrane was taken out and then soaked in deionized water for 2 hours to obtain PVA-SF hydrogel (named PSD).

[0074] Under the conditions of Example 4, from Figure 8 It can be seen that PSD hydrogel has a chaotic fiber structure. Figure 2 The tensile stress-strain curve and Figure 3 , Figure 4 The statistical results show that the PSD hydrogel has a fracture strain of 85.99%, a tensile strength of 3.38 MPa, an elastic modulus of 9.08 MPa, and a thermal conductivity of 2.56 MJ / m 3 The work of fracture. Figures 10-12 The Fourier transform infrared spectrum of the hydrogel and its quantitative results show that the hydrogel has a peak at 3210 cm -1 The peak area at 3370 cm-1 accounts for 44.06%, and the peak area at 3370 cm-1 accounts for 44.06%. -1The peak area at SF is 55.94%, the content of β-sheet in SF is 21.38%, the content of random coil and spiral is 35.01%, and the content of β-turn is 43.61%. Compared with Examples 2 and 3, its mechanical properties are weaker.

[0075] Example 5

[0076] Weigh 20 g of polyvinyl alcohol (molecular weight 146,000-186,000) powder and mix with 980 mL of deionized water, heat and stir in an oil bath at 110 °C for 12 h to prepare a 2 wt% PVA solution;

[0077] The PVA solution was injected into a polytetrafluoroethylene mold (10 cm × 10 cm × 5 mm), and the mold was dried on a 40°C constant temperature heating platform for 24 h;

[0078] The formed PVA film was immersed in deionized water to obtain a PVA hydrogel (named as PVA).

[0079] Under the conditions of Example 5, from Fig. 9 From the microscopic morphology of PVA hydrogel, we can see that there is no fiber distribution structure. Figure 2 The tensile stress-strain curve and Figure 3 , Figure 4 The statistical results show that PVA hydrogel has a fracture strain of 317.99%, a tensile strength of 1.35 MPa, an elastic modulus of 0.31 MPa, and a thermal conductivity of 1.86 MJ / m 3 The work of fracture. Figures 10-11 The Fourier transform infrared spectrum of the hydrogel and its results show that the hydrogel has a wavelength of 3210 cm -1 The peak area at 3370 cm-1 accounts for 39.81%, and the peak area at 3370 cm-1 accounts for 39.81%. -1 The peak area at 3210 cm-1 accounts for 60.19% compared with Examples 2, 3, and 4. -1 The peak ratio is the smallest, so the mechanical properties are the weakest. Since SF is not added in Example 5, the prepared hydrogel does not have the corresponding structure in Examples 2, 3, and 4. Fig.18 It can be found that the hydrogel prepared under the conditions of Example 5 also has good cell compatibility.

[0080] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. Oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel, characterized in that: The hydrogel comprises degummed silk fibers and polyvinyl alcohol, the mass ratio of the degummed silk fibers to the polyvinyl alcohol is 1:1 to 1:4, and the hydrogel has an anisotropic structure.

2. The method for preparing the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel according to claim 1, characterized in that: The specific method is as follows: the degummed silk fibers are oriented and then degummed, combed and dispersed evenly with a comb, and then placed in a polytetrafluoroethylene mold, and polyvinyl alcohol solution is poured into it, and evaporated on a constant temperature heating platform to obtain a hydrogel dry film, which is then heat-pressed on a hot press, and finally swelled in deionized water to obtain a hydrogel.

3. The method for preparing the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel according to claim 2, characterized in that: The molecular weight of the polyvinyl alcohol solution is 1000-500000, the concentration of the polyvinyl alcohol solution is 0.2-20 wt %, the mass ratio of the degummed silk fiber to the polyvinyl alcohol solution is 1:1-1:4, and the degummed silk fiber is obtained by degumming white silk.

4. The method for preparing the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel according to claim 2, characterized in that: The temperature of the constant temperature heating platform is 30-90°C, and the temperature of the thermal annealing is 90-150°C.

5. Use of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel in the preparation of an artificial intervertebral disc as claimed in claim 1, characterized in that: The specific preparation method comprises the following steps: S1, multiple sheets of oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel were stacked and bonded with polyvinyl alcohol as glue; S2, compacting the laminated oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel with a breathable ceramic sheet, placing it in an oven for drying, and surrounding the laminated layer after compaction and drying into an artificial fiber ring; S3, thermally annealing the artificial annulus fibrosus and allowing it to swell in deionized water, and dripping agarose solution into the artificial annulus fibrosus to obtain an artificial intervertebral disc hydrogel material.

6. Use of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel in the preparation of an artificial intervertebral disc as claimed in claim 5, characterized in that: In the step S1, the stacking angle between the multiple pieces of oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel is 30°, 45° or 60°.

7. Use of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel in the preparation of an artificial intervertebral disc as claimed in claim 5, characterized in that: In the step S1, the glue is a 10 wt% polyvinyl alcohol aqueous solution.

8. Use of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel in the preparation of an artificial intervertebral disc as claimed in claim 5, characterized in that: In the step S2, the drying temperature is 60°C and the thermal annealing temperature is 110°C.

9. Use of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel in the preparation of an artificial intervertebral disc as claimed in claim 5, characterized in that: In step S3, the concentration of the agarose solution is 5 wt %.

10. Use of the oriented degummed silk fiber reinforced polyvinyl alcohol hydrogel as claimed in claim 1 in the field of medical materials.

Citation Information

Patent Citations

  • Silk fibroin and polyvinyl alcohol blending antibacterial nanometer fiber and its preparation method

    CN101187089A

  • Polyvinyl alcohol hydrogel and preparation method thereof

    CN107185051A

  • Fluorescent nano dressing and preparation method thereof

    CN114470300A

  • Cartilage-imitating hydrogel electrode material, preparation method and supercapacitor

    CN116453869A

  • Tough composite hydrogel film as well as preparation method and application thereof

    CN118515902A

Cited By

  • PH-responsive hydrogel as well as preparation method and application thereof

    CN120919036A